Engaging Nigerian Workers and Other Stakeholders as Strategic Partners in Driving the Process of Reforms in the Public Sector - Esidene, Erunke Canice; Abdul, Abdullahi Mohammed; Sadiq, Yahaya Abubakar; Etaoghenevwegba, Oyibode Gabriel Chukwuma (Kashere Journal of Politics and International Relations, 2023)
The main objective of this paper is to examine the relationship between the engagement of Nigerian workers and other stakeholders as strategic partners in the nation’s public sector reform process, and how the employees can become veritable tools for driving the process of change in the reforms. The unfortunately, the average worker in Nigeria, right from the colonial days, and to the present democratic dispensation, has not been adequately represented in the decision making organogram that should be able to drive the desired change in public sector reforms. This study finds that the neglect of Nigerian workers in virtually all public sector reforms processes is evidently responsible for abysmal failure deliver on their mandates. This is because reforms architecture lacks the essential ingredients of democratization, interest aggregation and corporate governance. This paper is a theoretical exposition of works of renowned experts in the broader field of public sector administration. The work relies on secondary sources as method employed for research investigation. Among other things, the study recommends for adequate representation of the collective interests of Nigerian workers in the affairs of reforms, inclusion of employees in the process of design and implementation of public sector reforms stakeholders who unarguably constitute valuable resource base for the survival of the public policies. This way, the public sector will, no doubt, experience increasing progress and sustainability in relation to reforms in all its ramifications.